Did the COVID-19 Pandemic Affect the Emergency Service and Outpatient Clinic Applications of Pediatric Patients? - Damla Geçkalan; Rahmi Özdemir (Galenos Yayinevi, 2022)
Introduction:In the Coronavirus disease-2019 (COVID-19) pandemic, hospital admission rates was observed same difference in due to masks, closure of schools, and curfews. In our study; we aimed to compare the pediatric health and diseases department applications, triage, diagnosis distribution and hospitalization rates during the pandemic period with those before the pandemic.Methods:In this study, 240.440 patients who applied to Kütahya Health Sciences University Hospital Pediatrics Department between 11.03.2019 and 11.03.2021 were evaluated retrospectively. The patients were analyzed in two groups as pre-pandemic and pandemic period. Diagnosis distribution was evaluated in October-November- December. Chi-square test was used to compare categorical variables, and multiple comparisons were analyzed using Bonferronicorrected Z-test. Significance level was acceppted as p<0.050. Ethics committee approval was obtained for the study.Results:Pediatrics department visits decreased by 68.5% during the pandemic period (p<0.001). During the pandemic period, while the rate of application to pediatric clinic, endocrinology and neonatal intensive care units increased and the rate of admission to pediatric emergency, allergy and cardiology departments decreased (p<0.001). While the diagnoses of respiratory tract infections, nausea-vomiting, cough, and fever were high before the pandemic. Gastroenteritis, urinary system infection, headache, constipation, urticaria, and neonatal hyperbilirubinemia were high in the pandemic period (p<0.001). Hospitalization rates during the pandemic period; it was determined that while the rates of pediatrics, allergy and cardiology hospitalizations decreased, the rate of hospitalization in emergency and neonatal intensive care units increased (p<0.001). No difference was found between mortality rates in pediatric and neonatal intensive care units (p=1.00). It was analyzed that while the green area application rate was higher before the pandemic, the yellow and red area application rate was higher during the pandemic period (p<0.001).Conclusion:While the rates of admission in pediatric patients decreased significantly during the pandemic period, it was thought that other respiratory tract infections decreased due to the closure of masks and schools. In addition, measures and seasonal arrangements should be made to reduce the applications for green area in the pediatric emergency services.